Sanitation conditions in the municipality of Conceição Do Araguaia and its impacts on the prevention of Covid-19 (Research, Society and Development, 2021)
To protect itself from contagion with the virus, society had to adapt to a new reality, developing new social and hygiene habits. However, this adaptation becomes difficult when considering how weaknesses occur in access to minimum basic sanitation conditions in many Brazilian cities, especially on the outskirts of capitals and inland cities, such as the city of Conceição do Araguaia, in the state of Pará. The objective of the study is to create a database that can be used to assist as decision recovery of the health departments (municipal and state) for control actions in the face of measures to combat the pandemic related to sewage and drainage, with a view to relationship between basic sanitation and Covid-19 contagion. The research methodology adopted for data collection the application of a structured questionnaire, with most of the questions closed, in order to make it possible to transform a series of qualitative facts (called attributes) into a series of quantitative values (called variables) thus allowing data analysis. The results showed that investment in the expansion of drainage and sewage infrastructure is still necessary as a strategy to mitigate the spread of SARS-CoV-2 in the city of Conceição do Araguaia, in the State of Pará. And, that access to basic sanitation is of great importance for actions to combat Covid-19.